Public Speaking Tools - Ricky Telg (EDIS)
When making a public speech, there are various tools at your disposal: vocal delivery, body language, visual aids, audience engagement, and the method of delivery. This 3-page fact sheet provides some suggestions about how to make good use of these tools. Written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, August 2011.